![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\dfrac{\sqrt{x}-2}{2\sqrt{x}+1}\) với \(x\ge0\)
Ta có: \(P-1=\dfrac{\sqrt{x}-2}{2\sqrt{x}+1}-1=\dfrac{\sqrt{x}-2-2\sqrt{x}-1}{2\sqrt{x}+1}=-\dfrac{\sqrt{x}+3}{2\sqrt{x}+1}\)
Do \(\sqrt{x}\ge0;\forall x\ge0\)
\(\Rightarrow\dfrac{\sqrt{x}+3}{2\sqrt{x}+1}>0\Rightarrow-\dfrac{\sqrt{x}+3}{2\sqrt{x}+1}< 0\)
\(\Rightarrow P-1< 0\Rightarrow P< 1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Sửa đề: \(P=\left(\dfrac{x}{2x-2}+\dfrac{3-x}{2x^2-2}\right):\left(\dfrac{x+1}{x^2+x+1}+\dfrac{x+2}{x^3-1}\right)\)\(P=\left(\dfrac{x}{2\left(x-1\right)}+\dfrac{3-x}{2\left(x-1\right)\left(x+1\right)}\right):\dfrac{\left(x+1\right)\left(x-1\right)+x+2}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(=\dfrac{x\left(x+1\right)+3-x}{2\left(x-1\right)\left(x+1\right)}:\dfrac{x^2-1+x+2}{\left(x-1\right)\left(x^2+x+1\right)}\)
\(=\dfrac{x^2+3}{2\left(x-1\right)\left(x+1\right)}\cdot\dfrac{\left(x-1\right)\left(x^2+x+1\right)}{x^2+x+1}\)
\(=\dfrac{x^2+3}{2\left(x+1\right)}\)
b: P=3
=>x^2+3=6(x+1)=6x+6
=>x^2-6x-3=0
=>\(x=3\pm2\sqrt{3}\)
c: P>4
=>P-4>0
=>\(\dfrac{x^2+3-8\left(x+1\right)}{2\left(x+1\right)}>0\)
=>\(\dfrac{x^2-8x-5}{x+1}>0\)
TH1: x^2-8x-5>0 và x+1>0
=>x>-1 và (x<4-căn 21 hoặc x>4+căn 21)
=>-1<x<4-căn 21 hoặc x>4+căn 21
Th2: x^2-8x-5<0 và x+1<0
=>x<-1 và (4-căn 21<x<4+căn 21)
=>Vô lý
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ĐKXĐ: x>=0
\(P-1=\dfrac{\sqrt{x}-2}{2\sqrt{x}+1}-1\)
\(=\dfrac{\sqrt{x}-2-2\sqrt{x}-1}{2\sqrt{x}+1}=\dfrac{-\sqrt{x}-3}{2\sqrt{x}+1}\)
\(=-\dfrac{\left(\sqrt{x}+3\right)}{2\sqrt{x}+1}< 0\)
=>P<1
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(P=1:\left(\dfrac{x+2}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}+\dfrac{\sqrt{x}+1}{x+\sqrt{x}+1}-\dfrac{1}{\sqrt{x}-1}\right)\)
\(=1:\dfrac{x+2+x-1-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\)
\(=\dfrac{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}{\sqrt{x}\left(\sqrt{x}-1\right)}=\dfrac{x+\sqrt{x}+1}{\sqrt{x}}\)
b: \(P-3=\dfrac{x-2\sqrt{x}+1}{\sqrt{x}}=\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}}>0\)
=>P>3
![](https://rs.olm.vn/images/avt/0.png?1311)
1: \(B=\dfrac{\sqrt{x}-1}{\sqrt{x}-2}-\dfrac{5\sqrt{x}-8}{\sqrt{x}\left(\sqrt{x}-2\right)}\)
\(=\dfrac{x-\sqrt{x}-5\sqrt{x}+8}{\sqrt{x}\left(\sqrt{x}-2\right)}=\dfrac{\left(\sqrt{x}-2\right)\left(\sqrt{x}-4\right)}{\sqrt{x}\left(\sqrt{x}-2\right)}\)
\(=\dfrac{\sqrt{x}-4}{\sqrt{x}}\)
2: \(P=A\cdot B=\dfrac{x+\sqrt{x}+1}{\sqrt{x}}\)
\(\Leftrightarrow P-2=\dfrac{x-\sqrt{x}+1}{\sqrt{x}}>0\)
=>P>2